Social responsibility of small and medium-sized business in Russia - A V Neverov; E S Davydenkova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2016)
Corporate social responsibility has become an important part of business activities of many organizations. Despite the fact that the corporate social responsibility as an institutionalized organizational management process has existed for more than 50 years, it has not yet received the deserved scientific attention, and its various aspects are still subject to debates. Given that small and medium-sized business organizations play an important role in the socio-economic development of the country, such a problem can become a significant barrier for increasing the efficiency of interaction of main actors and stakeholders of business activities in the country. Thus, it is crucial to study the priorities of small and medium-sized organizations in the corporate social responsibility field. The authors conducted an empirical exploratory study of the Russian small and medium-sized business organizations and found out that their representatives do not have a clear understanding of the directions and methods of implementing the social responsibility model. For instance, the standards developed for large organizations to implement the ideas of corporate social responsibility are too global and too costly for small and medium-sized businesses, however the latter in Russia still do not have their own technologies and algorithms for implementing an appropriate model of social responsibility (except for some types of charity and requirements to retrain workers, which are considered rather external claims).